2005
DOI: 10.1042/bj20050681
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450/NADPH-dependent biosynthesis of 5,6-trans-epoxyeicosatrienoic acid from 5,6-trans-arachidonic acid

Abstract: 5,6-trans-AA (5,6-TAA, where TAA stands for trans-arachidonic acid) is a recently identified trans fatty acid that originates from the cis-trans isomerization of AA initiated by the NO2 radical. This trans fatty acid has been detected in blood circulation and we suggested that it functions as a lipid mediator of the toxic effects of NO2. To understand its role as a lipid mediator, we studied the metabolism of 5,6-TAA by liver microsomes stimulated with NADPH. Profiling of metabolites by liquid chromatography/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Enzymes in the cytochrome P450 (CYP) 2 superfamily are involved in the monooxygenation of a diverse repertoire of foreign and endogenous compounds. Of the 57 human enzymes in this superfamily, perhaps a third to a fourth are responsible for the metabolism of xenobiotics, including pharmaceuticals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes in the cytochrome P450 (CYP) 2 superfamily are involved in the monooxygenation of a diverse repertoire of foreign and endogenous compounds. Of the 57 human enzymes in this superfamily, perhaps a third to a fourth are responsible for the metabolism of xenobiotics, including pharmaceuticals.…”
mentioning
confidence: 99%
“…In fact, the action of CYP2E1 on acetaminophen creates a metabolite responsible for hepatotoxicity and death in acetaminophen overdose cases. However, CYP2E1 is also known to oxidize endogenous fatty acids, including lipids associated with signaling mechanisms such as arachidonic acid (1) and epoxyeicosatrienoic acids (2). Specifically, biochemical investigations have revealed that CYP2E1 can bind a range of mid-length fatty acids and catalyze the (primarily -1) hydroxylation of saturated fatty acids and the epoxidation of the alkenes of unsaturated fatty acids.…”
mentioning
confidence: 99%
“…These substrates include industrial solvents such as benzene, toluene, aniline, and halogenated solvents (18); alcohols such as ethanol (19), glycerol, phenol, and p-nitrophenol (20); and bicyclic heterocycles such as caffeine (21) and the muscle relaxant chlorzoxazone (22). However, CYP2E1 is also known to metabolize endogenous fatty acids, including lipids associated with signaling mechanisms such as arachidonic acid (23) and epoxyeicosatrienoic acids (24). The role of CYP2E1 in the metabolism of these signaling molecules may be related to its regulation by disease states such as obesity (25) and diabetes (26) in rat models.…”
mentioning
confidence: 99%
“…Because 13-H-14,15-EETA has a hydroxyl group separating the double bond and the epoxide group, it can be postulated that the hydroxyl group protects the epoxide from acid hydrolysis by a combination of steric shielding and inductive effects. Additionally, 5,6-trans-EET is more stable and resistant to hydrolysis than its cis-isomer (45). Thus, the trans-epoxide of 13-H-14,15-EETAs could also contribute to the acid stability.…”
Section: Discussionmentioning
confidence: 99%